The Power of Dai- Dai Virtual: Peran Dakwah dalam Literasi Pesan terkait Covid 19 di Era Post Truth - Khadijah Arnus, Sri; Prio Utomo, Agus; Mamis, Subriah (IAIN Madura, 2022)
Facts and news hoaxes about Covid-19 are widely scattered in the media. This creates panic and confusion in the audience. In the midst of public confusion about the confusion of information, on the other hand the figure of a preacher or